Which outcomes are important to patients and families who have experienced paediatric acute respiratory illness? Findings from a mixed methods sequential exploratory study. Issue 12 (14th December 2017) - Dyson, Michele P; Shave, Kassi; Gates, Allison; Fernandes, Ricardo M; Scott, Shannon D; Hartling, Lisa
Abstract : Objectives: To identify the outcome priorities of parents of children who had experienced an acute respiratory infection (ARI). Design: This was a two-phase, mixed methods study with a sequential exploratory design. We used a cross-sectional quantitative web-based survey to elicit parents' priorities for paediatric ARI. We then used a discussion moderated via Facebook to elucidate richer descriptions of parents' priorities. Setting: Survey and discussion data were collected via the internet. Participants: 110 parents (90% women, median age 35 years, 92.7% urban dwelling, 94.5% with a postsecondary education) with a child who had experienced an ARI responded to the survey. Four parents participated in the Facebook discussion. Primary and secondary outcome measures: The primary outcome was parents' rankings of outcomes related to paediatric ARI. The secondary outcomes were the alignment of parent-reported important outcomes with those commonly reported in Cochrane systematic reviews (SRs). Results: Commonly reported ARIs included croup (44.5%), wheezing (43.6%) and influenza (38.2%). Parents ranked major complications, illness symptoms and length of stay as the most important outcome categories. With respect to specific outcomes, severe complications, major side effects, doctor's assessment, relapse, oxygen supplementation and results from laboratory measures were reported as most important (75th–99th percentile). Taking time off work, mild complications, interference with daily activities, treatment costs, absenteeism, follow-up visits and other costs were deemed minimally important (<25th percentile). In 35 Cochrane SRs, 29 unique outcomes were reported. Although participants' priorities sometimes aligned with outcomes frequently reported in the literature, this was not always true. Additional priorities from the survey (n=50) and Facebook discussions (n=4) included healthcare access, interacting with healthcare providers, education, impact on daily activities and child well-being. Conclusions: In the context of paediatric ARI, parents' priorities did not always align with commonly researched outcomes. Appealing and efficient strategies to engage patients and parents in research should be developed.